Synthesis, characterization and in silico studies of some schiff’s bases derived from amino acids - E. Mohana Roopa (International Journal of Pharmacy and Analytical Research, 2016)
The project is aimed at the synthesis of some schiff bases derived from some aldehydes with amino acids such as glycine and alanine. This method is applied successfully to the synthesis of six imines from compounds. The structures of these Schiff bases are confirmed by using physical methods, namely, melting point or boiling point, UV and IR spectra. The physicochemical properties and possible biological activities are predicted using i lab 2 and PASS softwares.